Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Certainly! Let's differentiate the function [tex]\(y = \frac{2x}{5 - \tan(x)}\)[/tex] with respect to [tex]\(x\)[/tex]. Follow these steps:
### Step-by-Step Differentiation:
1. Identify the function:
[tex]\[ y = \frac{2x}{5 - \tan(x)} \][/tex]
2. Apply the Quotient Rule:
The Quotient Rule for differentiation states that if you have a function of the form [tex]\(\frac{u}{v}\)[/tex], where [tex]\(u\)[/tex] and [tex]\(v\)[/tex] are functions of [tex]\(x\)[/tex],
[tex]\[ \left( \frac{u}{v} \right)' = \frac{v \cdot u' - u \cdot v'}{v^2} \][/tex]
Here, [tex]\(u = 2x\)[/tex] and [tex]\(v = 5 - \tan(x)\)[/tex].
3. Differentiate [tex]\(u\)[/tex] and [tex]\(v\)[/tex]:
- [tex]\(u = 2x\)[/tex], so [tex]\(u' = 2\)[/tex]
- [tex]\(v = 5 - \tan(x)\)[/tex], so [tex]\(v' = -\sec^2(x)\)[/tex] (since the derivative of [tex]\(\tan(x)\)[/tex] is [tex]\(\sec^2(x)\)[/tex])
4. Substitute [tex]\(u\)[/tex], [tex]\(u'\)[/tex], [tex]\(v\)[/tex], and [tex]\(v'\)[/tex] into the Quotient Rule:
[tex]\[ \frac{d}{dx} \left( \frac{2x}{5 - \tan(x)} \right) = \frac{(5 - \tan(x)) \cdot 2 - 2x \cdot (-\sec^2(x))}{(5 - \tan(x))^2} \][/tex]
5. Simplify the numerator:
[tex]\[ = \frac{2(5 - \tan(x)) + 2x \cdot \sec^2(x)}{(5 - \tan(x))^2} \][/tex]
6. Further simplify:
[tex]\[ = \frac{10 - 2\tan(x) + 2x \sec^2(x)}{(5 - \tan(x))^2} \][/tex]
7. Combine like terms:
[tex]\[ = \frac{2x \sec^2(x) + 10 - 2\tan(x)}{(5 - \tan(x))^2} \][/tex]
Thus, the derivative [tex]\(\frac{dy}{dx}\)[/tex] of the function [tex]\(y = \frac{2x}{5 - \tan(x)}\)[/tex] is:
[tex]\[ \boxed{\frac{2x \sec^2(x) + 10 - 2\tan(x)}{(5 - \tan(x))^2}} \][/tex]
### Step-by-Step Differentiation:
1. Identify the function:
[tex]\[ y = \frac{2x}{5 - \tan(x)} \][/tex]
2. Apply the Quotient Rule:
The Quotient Rule for differentiation states that if you have a function of the form [tex]\(\frac{u}{v}\)[/tex], where [tex]\(u\)[/tex] and [tex]\(v\)[/tex] are functions of [tex]\(x\)[/tex],
[tex]\[ \left( \frac{u}{v} \right)' = \frac{v \cdot u' - u \cdot v'}{v^2} \][/tex]
Here, [tex]\(u = 2x\)[/tex] and [tex]\(v = 5 - \tan(x)\)[/tex].
3. Differentiate [tex]\(u\)[/tex] and [tex]\(v\)[/tex]:
- [tex]\(u = 2x\)[/tex], so [tex]\(u' = 2\)[/tex]
- [tex]\(v = 5 - \tan(x)\)[/tex], so [tex]\(v' = -\sec^2(x)\)[/tex] (since the derivative of [tex]\(\tan(x)\)[/tex] is [tex]\(\sec^2(x)\)[/tex])
4. Substitute [tex]\(u\)[/tex], [tex]\(u'\)[/tex], [tex]\(v\)[/tex], and [tex]\(v'\)[/tex] into the Quotient Rule:
[tex]\[ \frac{d}{dx} \left( \frac{2x}{5 - \tan(x)} \right) = \frac{(5 - \tan(x)) \cdot 2 - 2x \cdot (-\sec^2(x))}{(5 - \tan(x))^2} \][/tex]
5. Simplify the numerator:
[tex]\[ = \frac{2(5 - \tan(x)) + 2x \cdot \sec^2(x)}{(5 - \tan(x))^2} \][/tex]
6. Further simplify:
[tex]\[ = \frac{10 - 2\tan(x) + 2x \sec^2(x)}{(5 - \tan(x))^2} \][/tex]
7. Combine like terms:
[tex]\[ = \frac{2x \sec^2(x) + 10 - 2\tan(x)}{(5 - \tan(x))^2} \][/tex]
Thus, the derivative [tex]\(\frac{dy}{dx}\)[/tex] of the function [tex]\(y = \frac{2x}{5 - \tan(x)}\)[/tex] is:
[tex]\[ \boxed{\frac{2x \sec^2(x) + 10 - 2\tan(x)}{(5 - \tan(x))^2}} \][/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.